Of three sharks and one chimaera: varied habitat preferences across a latitudinal range revealed by coastal and offshore surveys. Issue 3 (10th January 2022) - Jac, Romaric; Höffle, Hannes; Albretsen, Jon; Jakobsdóttir, Klara; Staby, Arved; Søvik, Guldborg; Junge, Claudia
Abstract: Using national and international research survey data and applying a combination of models and mapping tools, this study revealed temperature and depth as the crucial environmental drivers of both the distribution and the abundance of four benthopelagic chondrichthyans inhabiting Norwegian and Icelandic waters: rabbitfish ( Chimaera monstrosa ), velvet‐belly lanternshark ( Etmopterus spinax ), blackmouth catshark ( Galeus melastomus ) and spurdog ( Squalus acanthias ). C. monstrosa and E. spinax seem to prefer similar spatial and ecological habitats, that is deep and cold waters. In contrast, G. melastomus and S. acanthias both prefer similar ecological habitats, that is warmer and shallower waters; nonetheless, they exhibit a different spatial distribution pattern. The species' varied habitat and spatial preferences may lead to different levels of exposure to fishing activities and associated by‐catch risks. Findings of the species' spatial distributions and their driving forces are expected to inform the sustainable management of these species and the ecosystems they inhabit.